Vincent Van Gogh : He Saw the World in Vibrant Colors - Guglielmo, Amy; Braun, Petra (Children's book illustrator) (New York, NY : DK Publishing, 2021)
Young children can meet Dutch painter Vincent van Gogh and learn what led him to paint his striking self-portraits and the landscapes that inspired his iconic Wheat Fields.
Keywords: Gogh, Vincent van, -- 1853-1890 -- Juvenile literature; Gogh, Vincent van, -- 1853-1890; Gogh, Vincent van, -- 1853-1890; Artists -- Juvenile literature. -- Netherlands; Artists -- Netherlands; Biographies; Juvenile works; Biographies